Centro de formación juvenil barrio Las Acacias - Sghirla Uvidia, Leslie Nataly (2018)
Graduate project is based on the development of the territorial planning plan for the axis of the August 10th Avenue developed by the ninth-semester project workshop (ARO-960). In order to develop an urban proposal through micro-centers, a plan is presented with various equipment that make up these micro-centers. Once the conclusions have been analyzed, a deficit of sociocultural welfare facilities is determined, where the Training center for young people equipment in the Maldonado neighborhood is proposed. The equipment responds to a social exclusion of young people due to a lack of cultural identity, being victims of vulnerability that generate feelings of abandonment and that do not have any kind of support. The problems of the young settle in a lack of cultural identity, taking into account several problems were raised strategy that focuses mainly on generating several spaces of interest for young people, and thereby strengthen the cultural identity, helping them to generate self-evident spaces that they are a reflection of everything they need, through spaces that allow activities of cultural and corporal artistic recreation.